Analyzing Vaccine Trials in Epidemics With Mild and Asymptomatic Infection. Issue 2 (17th October 2018) - Kahn, Rebecca; Hitchings, Matt; Wang, Rui; Bellan, Steven E; Lipsitch, Marc
Abstract: Vaccine efficacy against susceptibility to infection (VE S ), regardless of symptoms, is an important endpoint of vaccine trials for pathogens with a high proportion of asymptomatic infection, because such infections may contribute to onward transmission and long-term sequelae, such as congenital Zika syndrome. However, estimating VE S is resource-intensive. We aimed to identify approaches for accurately estimating VE S when limited information is available and resources are constrained. We modeled an individually randomized vaccine trial by generating a network of individuals and simulating an epidemic. The disease natural history followed a "susceptible-exposed-infectious/symptomatic (or infectious/asymptomatic)-recovered" model. We then used 7 approaches to estimate VE S, and we also estimated vaccine efficacy against progression to symptoms (VE P ). A corrected relative risk and an interval-censored Cox model accurately estimate VE S and only require serological testing of participants once, while a Cox model using only symptomatic infections returns biased estimates. Only acquiring serological endpoints in a 10% sample and imputing the remaining infection statuses yields unbiased VE S estimates across values of the basic reproduction number ( R 0 ) and accurate estimates of VE P for higher R 0 values. Identifying resource-preserving methods for accurately estimating VE S and VE P is important in designing trials for diseases with a high proportion of asymptomatic infection.